Characterization of a population of neural progenitor cells in the infant hippocampus. Issue 5 (August 2014) - Paine, Simon M. L.; Willsher, Alex R.; Nicholson, Sarah L.; Sebire, Neil J.; Jacques, Thomas S.
<x xml:space="preserve">Abstract</x> Aims Abnormalities of the hippocampus are associated with a range of diseases in children, including epilepsy and sudden death. A population of rod cells in part of the hippocampus, the polymorphic layer of the dentate gyrus, has long been recognized in infants. Previous work suggested that these cells were microglia and that their presence was associated with chronic illness and sudden infant death syndrome. Prompted by the observations that a sensitive immunohistochemical marker of microglia used in diagnostic practice does not typically stain these cells and that the hippocampus is a site of postnatal neurogenesis, we hypothesized that this transient population of cells were not microglia but neural progenitors. Methods Using archived post mortem tissue, we applied a broad panel of antibodies to establish the immunophenotype of these cells in 40 infants dying suddenly of causes that were either explained or remained unexplained, following post mortem investigation. Results The rod cells were consistently negative for the microglial markers CD45, CD68 and HLA‐DR. The cells were positive, in varying proportions, for the neural progenitor marker, doublecortin, the neural stem cell marker, nestin and the neural marker, TUJ1. Conclusions These data support our hypothesis that the rod cells of the polymorphic layer of the dentate gyrus in the infant hippocampus are not microglia but a population of neural progenitors. These findings advance our understanding of postnatal neurogenesis in the human hippocampus in health and disease and are of diagnostic importance, allowing reactive microglia to be distinguished from the normal population of neural progenitors.